Sportstagram & Tiktok Athletic: FOMO Dan Lifestyle Digital Terhadap Self-Representation Melalui Aktivitas Olahraga Di Media Sosial - Sandira, Nur Fadilah Ayu; Sachrir, Muh. Irshan; Sarah, Nulthazam; Arifin Bando, Ushwa Dwi Masrurah (STIM-LPI Makassar, 2025)
Social media has changed the way individuals construct self-image, particularly through posts about physical activities such as exercise. This study aims to analyze the influence of Fear of Missing Out (FOMO) and lifestyle on self-representation on social media, with exercise activity as a mediating variable. This study used a quantitative, explanatory approach and involved 200 respondents from Generation Z and millennials who actively share exercise activities on Instagram and TikTok. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that FOMO has no direct influence on self-representation, but does have an indirect influence through exercise activity. Conversely, lifestyle has both direct and indirect effects on self-representation. Exercise activity proved to be a significant mediator in shaping digital self-image. These findings confirm that self-representation on social media is not only driven by social pressures such as FOMO, but also by engagement in meaningful, real-life activities. This research contributes to the study of digital consumer behavior, as well as practical implications for lifestyle and community-based marketing strategies.